2016
DOI: 10.1088/0963-0252/25/6/065026
|View full text |Cite
|
Sign up to set email alerts
|

Electric field measurements in a kHz-driven He jet—the influence of the gas flow speed

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
91
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(107 citation statements)
references
References 64 publications
15
91
0
1
Order By: Relevance
“…Ionization wave emits light only from the ionization front-streamer head. Consequently, spatially resolved measurement also reveals a temporal development of the streamer as it was argued by Sobota et al, 13 For example, in the mentioned article where the same discharge is investigated, spatio-temporally resolved electric field measurements were compared with the spatially resolved measurements. The overlap of the data initiated further integrated measurements in order to reduce the duration of time consuming measurements anyhow.…”
Section: Experimental Set-upmentioning
confidence: 93%
See 3 more Smart Citations
“…Ionization wave emits light only from the ionization front-streamer head. Consequently, spatially resolved measurement also reveals a temporal development of the streamer as it was argued by Sobota et al, 13 For example, in the mentioned article where the same discharge is investigated, spatio-temporally resolved electric field measurements were compared with the spatially resolved measurements. The overlap of the data initiated further integrated measurements in order to reduce the duration of time consuming measurements anyhow.…”
Section: Experimental Set-upmentioning
confidence: 93%
“…Atmospheric pressure helium plasma jet of coaxial geometry described in the previous articles is also used in this study. [13][14][15][16] It consists of Pyrex tube with inner diameter of 2.5 mm and outer diameter of 4 mm and two metallic electrodes. Powered electrode is stainless steel pipe with inner and outer diameters of 0.8 and 1.6 mm, respectively.…”
Section: Experimental Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…Another work suggests the charged species may be able to permeate significant distances from various APPJ sources. Sobota et al measured the electric field from a He APPJ and showed that it increased to a maximum point approximately 8 mm from the exit of the tube though this varied with gas flow and other parameters. Additionally it should be considered that if charged species are responsible for the enhanced etching at room temperature then the sample may become charged over the duration of the APPJ treatment.…”
Section: Discussionmentioning
confidence: 99%